143k views
11 votes
Solve the simultaneous equation:
2x - y= 2
3y= 4x - 5

User Detaylor
by
4.7k points

1 Answer

7 votes

Answer:

x =
(1)/(2) , y =
-1

Step-by-step explanation:

2x - y= 2

3y= 4x - 5

Make y the subject:

2x - y= 2

-y = 2 - 2x

y = 2x - 2 .........equation 1

3y= 4x - 5

y = (4x - 5)/3 ........equation 2

From equation 1 and 2 solve them simultaneously:

→ (4x - 5)/3 = 2x - 2

→ 4x - 5= 3(2x - 2)

→ 4x - 5 = 6x - 6

→ 6x - 4x = -5 + 6

→ 2x = 1

→ x = 1/2

  • if x is 1/2, then y: 2x - 2

→ 2(1/2)-2

→ -1

User Federico Scamuzzi
by
4.7k points